Thermal properties of biocomposites based on sea mango fibers - Koh, Jian Liang (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
The effect of sea mango (SM) filler loading and the effect of amount used of polypropylene-graft-maleic anhydride (PP-g-MA) added as a compatibilizer on thermal properties and flow behavior of biocomposites were studied. The compounding of polypropylene/sea mango biocomposites was carried out using different in weight percentage of sea mango filler based on composite and different weight percentage of PP-g-MA based on weight of polypropylene (PP).